Hospital-based bereavement care provision: A cross-sectional survey with health professionals. (April 2020) - Naef, Rahel; Peng-Keller, Simon; Rettke, Horst; Rufer, Michael; Petry, Heidi
Background: An in-hospital death is a profound experience for those left behind and has been associated with family members' psychological morbidity. Supporting bereaved family members is an essential part of end-of-life care and includes attentive presence, information-giving, and emotional and practical support. The actual adoption of hospital-based bereavement care, however, remains little understood. Aim: To investigate hospital-based bereavement care provision and associated barriers. Design: Cross-sectional survey using an online questionnaire. Setting/participants: Health professionals ( n = 196) from two University-affiliated acute and psychiatric hospitals in Switzerland. Results: The most frequent bereavement services (⩾40%) were viewing the deceased, giving information on available support, and making referrals; the most often named barriers were lack of time and organizational support. Acute care health professionals faced statistically significant more structural barriers (55.1% vs 21.4% lack of time, 47.8% vs 25.9% lack of organizational support) and felt insufficiently trained (38.4% vs 20.7%) compared to mental health professionals ( p ⩽ 0.05). Nurses provided more immediate services compared to physicians, such as viewing the deceased (71.3% vs 49.0%) and sending sympathy cards (37.4% vs 16.3%) ( p ⩽ 0.01). In contrast, physicians screened more often for complex bereavement disorders (10.2% vs 2.6%) and appraised bereavement care as beyond their role (26.5% vs 7.8%) ( p ⩽ 0.05). Conclusion: The study indicates that many barriers to bereavement care exist in hospitals. More research is required to better understand enabling and limiting factors to bereavement care provision. A guideline-driven approach to hospital-based bereavement care that defines best practice and required organizational support seems necessary to ensure needs-based bereavement care.